Screening and mechanistic study of natural compounds that enhance T cell anti-tumor effects post-heat treatment - Wang, Zhaoyi; Diao, Zhongqi; Zhang, Yiyan; Liu, Jiangying; Li, Yeshan; Sun, Zijin; Zhen, Huimin; Wang, Haojia; Yang, Siyun; Wang, Tieshan; Ni, Lei (Frontiers in Immunology, 2025)
IntroductionFollowing the approval of Chimeric Antigen Receptor T-cell Immunotherapy(CAR-T) in multiple countries, the Food and Drug Administration (FDA) approved tumor-infiltrating lymphocytes (TILs) and T-cell receptor-engineered T cells (TCR-T) treatments this year. The utilization of adoptive immunotherapy in tumor treatment has become increasingly prominent. Optimizing the cytotoxic effects of immune cells under in vitro culture conditions represents a current hot research topic in this domain.MethodsIn the current experiment, we conducted in vitro heat treatment on Jurkat-derived T cells at 39°C. On this basis, we utilized nine distinct injectable solutions and over 70 monomer components of Traditional Chinese Medicine (TCM). Subsequently, we co-cultured these treated Jurkat cells with K562-eGFP cells, and the co-culture process was monitored in real-time using the IncuCyte live-cell analysis system. Equally important, we combined HiMAP high-throughput transcriptome sequencing, proteomics, and metabolomics for in-depth examination. We screened for compounds possessing anti-tumor properties and thoroughly investigated their mechanisms of action.Results and DiscussionThe findings indicated that heating treatment augmented the cytotoxic effect of Jurkat cells against malignant tumors, and the optimal effect was achieved when T cells were exposed to 39°C for a duration of 24 hours(48% increase in cell proliferation rate compared to 37°C treatment). By triggering the generation of heat shock proteins and facilitating mitochondrial energy supply, the 39°C treatment amplified the anti-tumor functions of T cells. By analyzing the data, we identified 3 injectable solutions and more than 20 effective monomers capable of further enhancing the tumor-killing ability of T cells. High-throughput transcriptomics studies disclosed that the combination of thermotherapy and TCM promoted Jurkat cell proliferation, activation, and cytotoxic functions of Jurkat cells, thereby activating the Regulation of mitotic cell cycle to exert anti-tumor effects. The integration of transcriptomic and proteomic data demonstrated that Shengmai Injection significantly enhances the tumor-killing effect of Jurkat cells by down-regulating the Regulation of Apoptosis and Regulation of mitotic cell cycle signaling pathways.